Analisis Kebutuhan Media Poster Digital (PORTAL) dengan Location Direction untuk Meningkatkan Keterampilan Kronologis Siswa Pada Pembelajaran Sejarah di SMA - Novani, Adela; Yefterson, Ridho Bayu (Jurusan Sejarah FIS UNP, 2025)
The low chronological thinking skills of Grade XI F3 students at SMA Negeri 2 Sijunjung in history learning are reflected in their difficulties in sequencing events and connecting them with time and place. This condition is exacerbated by the dominance of lecture methods and the limited use of innovative media, making the learning process monotonous. This study aims to analyze the needs for developing Digital Poster (PORTAL) media with location direction features as an effort to enhance students’ chronological skills. The research employed a descriptive qualitative approach with data collected through classroom observation, teacher and student interviews, and questionnaires. The findings indicate that history learning remains confined to conventional media, causing students to become easily bored and struggle to understand the interrelation of events. Both teachers and students emphasized the need for visually engaging, interactive, and context-based media linked to historical locations. The study concludes that the development of Digital Poster (PORTAL) with location direction is highly relevant to support learning motivation and improve students’ chronological thinking skills in history learning.